Correlation Analysis between Women’s Body Mass Index and Mechanical Low Back Pain - Lydia Handini1 , Andriati1 , Subagyo1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Obesity can cause mechanical effects on spine, particularly lumbar spine, thus increased weight will cause spine, tendon and ligament muscle tensions. These problems can change lumbar curve with increased anterior pelvic tilt and hip flexion to maintain normal posture that may eventually cause low back pain. Women may experience weight gain, and it can cause low back pain. However, correlation between increased body mass index and low back pain is still debatable. Objective: The research aimed to analyze correlation between women’s body mass index and mechanical low back pain. Method: A total of 12 patients aged 50-60 were the subjects of the research. The subjects’ body mass index, pain scale and lumbosacral axis were measured. The study protocol was approved by the ethics committees of Dr. Soetomo Teaching Hospital (Surabaya, Indonesia). The correlation test was conducted using Pearson’s correlation test (Significant if p<0.05). Results: The research found no correlation between increased body mass index and low back pain (p = 0.47), while there was a correlation between increased body mass index and lumbosacral axis (p = 0.04). Moreover, there was no correlation between increased lumbosacral axis and low back pain (p = 0.07) Conclusion: The study found that the more the body mass index increased, the lumbosacral axis also increased, whereas no correlation between body mass index and low back pain.